A fracture mechanics approach to static and fatigue failure in glass reinforced plastics - Cann, Robert James (1977)
The aim of this project was to examine the application of fracture mechanics to static and fatigue failure in GRP. The performance of two materials commonly used in-shipbuilding was compared, and the stress intensity factor approach was chosen as being most useful in the design of GRP structures.